Do Patients With Personality Disorders Respond Differentially to Electroconvulsive Therapy?: A Review of the Literature and Consideration of Conceptual Issues. Issue 1 (March 2015) - Rasmussen, Keith G.
Abstract : Abstract: Personality disorders are common among depressed patients. While there is considerable research demonstrating that such patients may respond less optimally to antidepressant medications, there is a relative dearth of research on the outcomes of depressed personality-disordered patients treated with electroconvulsive therapy (ECT). In this review, the author summarizes the available reports and concludes that there is reasonably robust evidence that patients with borderline personality disorder experience lesser antidepressant responses to ECT acutely and probably higher post-ECT relapse rates than depressed patients with other or no personality disorders. Some of the complex issues involved in selecting and treating such patients are discussed, and recommendations are provided for clinical practice and future research.